2015
DOI: 10.1039/c4fd00251b
|View full text |Cite
|
Sign up to set email alerts
|

In situ monitoring of corrosion mechanisms and phosphate inhibitor surface deposition during corrosion of zinc–magnesium–aluminium (ZMA) alloys using novel time-lapse microscopy

Abstract: In situ time-lapse optical microscopy was used to examine the microstructural corrosion mechanisms in three zinc-magnesium-aluminium (ZMA) alloy coated steels immersed in 1% NaCl pH 7. Preferential corrosion of MgZn(2) lamellae within the eutectic phases was observed in all the ZMA alloys followed by subsequent dissolution of Zn rich phases. The total extent and rate of corrosion, measured using time-lapse image analysis and scanning vibrating electrode technique (SVET) estimated mass loss, decreased as Mg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 34 publications
1
79
0
Order By: Relevance
“…In situ time lapse optical microscopy, which allowed the imaging of immersed corroding samples at a microstructural level, was employed following a methodology developed previously [29][30] . MT8000 microscope was then manoeuvred so as to image the exposed sample area.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In situ time lapse optical microscopy, which allowed the imaging of immersed corroding samples at a microstructural level, was employed following a methodology developed previously [29][30] . MT8000 microscope was then manoeuvred so as to image the exposed sample area.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Moreover, the formation of simonkolleite is possible also in the presence of chlorides under atmospheric conditions. The protection mechanism of Mg‐containing Zn coatings has been also investigated under immersion conditions . It has been shown that magnesium delays the formation of zincite for Zn‐Mg‐Al coatings immersed in different electrolytes with pH 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The protection mechanism of Mg-containing Zn coatings has been also investigated under immersion conditions. [15,18,20,21,[23][24][25][26] It has been shown that magnesium delays the formation of zincite for Zn-Mg-Al coatings immersed in different electrolytes with pH 9. [19][20] This effect was attributed to the buffering effect of magnesium and to the rapid precipitation of magnesium hydroxide on the metallic coating.…”
Section: Introductionmentioning
confidence: 99%
“…Time-lapse Microscopy (TLM) was conducted using a Meiji MT8000 metallurgical microscope, fitted with an Infinity 2-5C camera. The technique has been well described in previous studies [149] [88] and in the experimental chapter. Once an NbC inclusion of suitable size was located (a set of three inclusions in a ≈20 µm 2 area was selected) , the specimen was connected to a Palmsens 3 potentiostat.…”
Section: Methodsmentioning
confidence: 96%
“…Breakdown potential at pit and crevice sites can be hundreds of millivolts lower than that of the metal surface; as a consequence of IR drop (which is related to pit and crevice geometry) [88]. These environments are more harsh than that of the bulk electrolyte, which help the continued aggressive growth of the excavation [13] [71].…”
Section: Nernst Equation and Pourbaixmentioning
confidence: 99%